The Element Of Forced Defense In Giving Reasons For Eliminating Crimes For Victims Of "Begal" According To Article 49 KUHP - I Komang Suardika; Anak Agung Gede Duwira Hadi Santosa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study was made to find out and analyze the elements that must be met in forced self-defense in accordance with Article 49 of the Criminal Code and the reasons for eliminating criminals for victims who carry out self-defense by force . The type of normative legal research is used in this study so that the approach taken is a statutory approach with primary, secondary and tertiary legal materials as legal material and the case approach is carried out by examining cases related to the legal issues at hand. The document study technique is used as a technique for collecting legal materials, then the legal materials are evaluated, interpreted, argued and discussed descriptively. The results of the study show (1) in accordance with Article 49 of the Criminal Code, the elements that must be fulfilled by someone who makes a forced defense to erase a crime or reduce his sentence are 1). The defense made must be forced. 2). Defending oneself, others, honor, decency and property, 3). There must be an attack or threat and 4). The attack is against the law and (2) the reason for the abolition of the crime consists of reasons for forgiveness and reasons for justification, to be able to apply the reason for the abolition of the criminal as a legal basis against someone who is forced to defend himself as contained in Article 49 of the Criminal Code by fulfilling various elements.